2017
DOI: 10.1002/jor.23597
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar multifidus muscle degenerates in individuals with chronic degenerative lumbar spine pathology

Abstract: Histological and cell-level changes in the lumbar musculature in individuals with chronic lumbar spine degenerative conditions are not well characterized. Although prior literature supports evidence of changes in fiber type and size, little information exists describing the tissue quality and biology of pathological features of muscle in this population. The purpose of this study was to quantify multifidus tissue composition and structure, inflammation, vascularity, and degeneration in individuals with chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
89
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 41 publications
10
89
4
Order By: Relevance
“…Despite the high proportion of markers for muscle recovery (centralized nuclei for regeneration and Pax7 + for satellite cell density), the number of muscle bers that exhibited degenerative characteristics remained high. This is consistent with previous results from our group that suggest the amount of muscle degeneration in chronic LBP patients outpaces the ability to restore a healthy muscle phenotype [10,63].…”
Section: Differences In Paraspinal Muscle Activation During Motion Ansupporting
confidence: 93%
See 2 more Smart Citations
“…Despite the high proportion of markers for muscle recovery (centralized nuclei for regeneration and Pax7 + for satellite cell density), the number of muscle bers that exhibited degenerative characteristics remained high. This is consistent with previous results from our group that suggest the amount of muscle degeneration in chronic LBP patients outpaces the ability to restore a healthy muscle phenotype [10,63].…”
Section: Differences In Paraspinal Muscle Activation During Motion Ansupporting
confidence: 93%
“…Markers of muscle vascularity, damage, and degeneration did not signi cantly differ between super cial and deep samples Although the average percentage of centralized nuclei for each biopsy level was higher than expected for healthy skeletal muscle (3%), this percentage was lower than values reported for other studies examining lumbar spine pathology [10,11]. Despite the high proportion of markers for muscle recovery (centralized nuclei for regeneration and Pax7 + for satellite cell density), the number of muscle bers that exhibited degenerative characteristics remained high.…”
Section: Differences In Paraspinal Muscle Activation During Motion Ancontrasting
confidence: 69%
See 1 more Smart Citation
“…Most studies of PS FI center on imaging quantification of FI and correlation to clinical outcomes. Those that include histology of tissue have focused primarily on general muscle fiber architecture and SCs . Therefore, the literature on FAP populations within PS muscle and their contributions to FI are scant.…”
Section: Discussionmentioning
confidence: 99%
“…Multifidus muscles biopsies were acquired from patients undergoing surgery. They concluded that changes in muscle tissue are more complex than simple atrophy including on average 48.5% muscle, 11.7% adipose tissue, and 26.1% collagen tissue, elevated inflammatory cells and decreased vascularity [22].…”
Section: Discussionmentioning
confidence: 99%